Prognostic Significance of Atrial Fibrillation in Lower Limb Amputee Patients. Issue 6 (December 2016) - Ralevic, S.; Perunicic, J.; Lasica, R.; Marinkovic, J.; Blagojevic, T.; Simanic, I.; Asanin, M.; Stankovic, G.
Abstract : Objective: In patients with risk factors or established atherothrombosis, atrial fibrillation (AF) is associated with a poor prognosis compared with patients without AF. The aim of this study was to evaluate the prevalence of AF in patients with lower limb amputation (LLA) and its association with cardiovascular death and adverse cardiovascular events in long-term follow-up. Methods: Observational prospective study of consecutive patients after index major (transfemoral and transtibial) LLA. The primary endpoint was cardiovascular death and secondary endpoint was a composite of adverse cardiovascular events at follow-up (acute myocardial infarction, contralateral lower limb amputation, and ischaemic stroke). Results: Of 282 patients with LLA, 46 (16.3%) patients had AF. AF patients were significantly older compared with patients without AF (median 74.0, IQR 13.0 vs. median 67.0, IQR 14.8 years, p  < .001). Diabetes and smoking on the other hand were significantly less prevalent in patients with AF compared with those without AF (41.3% vs. 72.0%, p  < .001 and 56.5% vs. 76.3%, p  = .01, respectively). 54.3% of patients with AF were on oral anticoagulation therapy. At a median follow-up of 24.0 months (IQR 19.0–32.0), 28.3% patients with AF died of cardiovascular causes versus 17.8% without AF (HRR 1.8, 95% CI 1.0–3.4, p  = .06). Adverse cardiovascular events occurred in 32.6% of patients with AF during follow-up versus 22.0% without AF (HRR 1.9, 95% CI 1.0–3.3, p  = .03). In multivariate Cox regression analysis, AF (HRR 2.3, 95% CI 1.3–4.2, p  = .01) and diabetes (HRR 2.1, 95% CI 1.1–3.9, p  = .02) were identified as independent predictors of adverse cardiovascular events during the follow-up. Conclusion: AF is common in patients with LLA and associated with higher risk of adverse cardiovascular events during long-term follow-up.